Oxaliplatin-related neuropathy in Indian patients – no difference between generic and original molecules - Sirohi, Bhawna; Ostwal, Vikas; Dawood, Shaheenah; Lopes, Gilberto; Talole, Sanjay; Nashikkar, Chaitali; Shrikhande, Shailesh (Indian Journal of Medical and Paediatric Oncology, 2016)
Background: Oxaliplatin-induced neuropathy is a dose-limiting toxicity that significantly affects patients' quality of life. The aim of this study was to compare its occurrence between a generic versus the original molecule in Indian patients. Materials and Methods: Between August 2012 and July 2013, 163 patients receiving oxaliplatin were prospectively enrolled. A data recording form was used in the clinic to record detailed information. Results: The median age of patients was 55 years (range, 19–79). Chemotherapy regimens used included: capecitabine, oxaliplatin (59), epirubicin, oxaliplatin, and capecitabine (20), docetaxel, oxaliplatin, and capecitabine (11), 5-FU, leucovorin, oxaliplatin (9), and gemcitabine-oxaliplatin (64). The median cumulative dose of oxaliplatin was 780 mg/m2. Eighty patients received the original version and 83 the generic one. Overall, 63 patients (38%) developed neuropathy. There was no significant difference in the incidence of neuropathy between the two forms of oxaliplatin used (P = 0.50). Forty-nine percent of female patients had neuropathy as compared to 30% of male patients (P = 0.014). Older patients had a trend toward a higher incidence of neuropathy: 44% of patients above age fifty developed neuropathy compared to 30% of patients younger than 50 (P = 0.06). Conclusion: This is the first study to specifically show that neuropathy rates do not vary with the use of generic versus original oxaliplatin.
Keywords: Generic; neuropathy; original molecule; oxaliplatin